عقد المضاربة في المعاملات المالية المعاصرة - Qibtiyatul Munawaroh (Qawanin: Jurnal of Economic Syaria Law, 2017)
The Mudarabah Company holds in the modern financial transactions of the contracts that are based on the honesty of the speculator in his work, and his honesty and sincerity, which are worthy qualities to instill in the hearts of traders and businessmen; because speculative is a great door for economic activity, where there are many people have the competence and ability to run the money And thus facilitate the contracts of speculation open the livelihoods of many workers and increase the movement of trade. Keywords: mudlarabah, financial transactions